2017
DOI: 10.1177/1010539517704042
|View full text |Cite
|
Sign up to set email alerts
|

Descriptive Epidemiology of Hypertension and Its Association With Obesity: Based on the WHO STEPwise Approach to Surveillance in Palau

Abstract: The rise of noncommunicable diseases is a serious health burden for Palau. This study described the prevalence of hypertension, and assessed its association with obesity. Surveys following the WHO STEPwise approach to surveillance were conducted in 2529 adults. Multivariate prevalence ratios (PR) of hypertension for body mass index (BMI) categories were calculated by logistic regression models using conditional standardization procedure. Age- and sex-specified analyses were performed. Overall prevalence of obe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 20 publications
0
2
0
1
Order By: Relevance
“…Moreover, hypertension is an insidious pathology, as its symptoms are difficult to detect. As a consequence, before correctly approaching this pathology, the hypertensive organ damage has time to develop [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Nutraceuticals In Hypertensionmentioning
confidence: 99%
“…Moreover, hypertension is an insidious pathology, as its symptoms are difficult to detect. As a consequence, before correctly approaching this pathology, the hypertensive organ damage has time to develop [ 23 , 24 , 25 , 26 , 27 , 28 ].…”
Section: Nutraceuticals In Hypertensionmentioning
confidence: 99%
“…Surveilans hipertensi dimaksudkan untuk menyediakan sumber informasi, diantaranya dengan mengambil data di website yang tidak disebutkan url di dalam artikelnya, kemudian di analisis mendalam terhadap data yang terkumpul dengan melihat pola histori dari kondisi pengumpulan data surveilans hipertensi (Shanbehzadeh et al, 2020). Sementara itu, surveilans hipertensi di Pulau Amerika Serikat menggambarkan indeks masa tubuh (Wang et al, 2017). Dengan demikian, surveilans hipertensi ditujukan untuk menggambarkan tekanan darah, tinggi badan, berat badan, masa indeks tubuh, glukosa darah/hemoglobin terglikasi, dan profil lipid.…”
Section: Surveilans Menurutunclassified
“…Therefore, in Palau, the government declared a state of health emergency to tackle NCD, then conducted the first national NCD survey, i.e., the World Health Organization (WHO) STEPwise approach to NCD risk factor surveillance (STEPS) 2011-2013 [7]. Previous studies analyzing this STEPS data suggested positive associations between obesity and NCDs [8][9][10][11].…”
Section: Introductionmentioning
confidence: 99%